Application of Naive Bayes Algorithm for Sentiment Analysis of Service and Facility Satisfaction (Case Study: PKU Muhammadiyah Sukoharjo General Hospital) - Putra, Hasda Surya; Vihi Atina; Dwi Hartanti (LPPM Telkom University Surabaya, 2024)
PKU Muhammadiyah Sukoharjo Hospital is a health facility located in Sukoharjo, Central Java. The role of the hospital in the Sukoharjo community is very important in terms of the level of community satisfaction with its services and facilities. Opinions and assessments from the community also affect the assessment of the quality of service provided by the hospital. A large assessment can be seen on Google Maps review, which will take time for the community. Public complaints on Google Maps review of PKU Muhammadiyah Sukoharjo Hospital became the basic object of this research. This research uses the Naive Bayes algorithm to categorize the assessment based on positive and negative sentiments. Two hundred nine review data from Google Maps were processed with text processing and classified using Naïve Bayes. Test results using 10% test data show a dominant positive sentiment, with 90% accuracy, 94% precision, and 83% recall.